2017
DOI: 10.1159/000464137
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Surgery: To Drain or Not to Drain, That Is the Problem - A Randomized Clinical Trial

Abstract: Purpose: We conducted a prospective, randomized study to evaluate the necessity of drainage after thyroid surgery. Methods: The patients (n = 215) were randomly assigned to be treated with suction drains (group 1; n = 108) or not (group 2; n = 107). Results: The postoperative pain scores were significantly lower in the non-drained group than in the drained group of patients at postoperative days 0 and at 1. Hematomas, seromas, wound infections, transient biochemical hypoparathyroidism, and transient damage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…Our other finding that drain placement is associated with a longer hospital stay is similarly consistent with available literature, with one study reporting a reduction in cost per patient as a result of not having a drain . Drain placement has also been associated with an increased rate of postoperative hypoparathyroidism, recurrent laryngeal nerve palsy, and wound infection, although these were not examined in our study . These observations are likely related to the experience and surgical volume of surgeons performing the procedure.…”
Section: Discussionmentioning
confidence: 80%
“…Our other finding that drain placement is associated with a longer hospital stay is similarly consistent with available literature, with one study reporting a reduction in cost per patient as a result of not having a drain . Drain placement has also been associated with an increased rate of postoperative hypoparathyroidism, recurrent laryngeal nerve palsy, and wound infection, although these were not examined in our study . These observations are likely related to the experience and surgical volume of surgeons performing the procedure.…”
Section: Discussionmentioning
confidence: 80%
“…Drains can generally lead to a reduction in pain after surgeries such as total knee arthroplasty, but the results in this randomized prospective study were only confirmed in the early-term but not long-term follow-up [17]. However, in considering the postoperative pain in other disciplines, Schietroma et al found that routine drain placement after thyroidectomy is not necessary, and avoiding drainage was associated with less postoperative pain [44]. The controversial results in between the trials mentioned above lead ultimately to different conclusions which are possibly subject-specific.…”
Section: Possible Complications and Side Effects After Placement Of Smentioning
confidence: 75%
“…This poses the question of whether drain volume is clinically relevant. Drains are used less often in modern thyroid surgery; a recent RCT suggested their use was unnecessary. The use of drains to reduce postoperative bleeding is seen to have no significant effect and may potentially prolong hospital stay.…”
Section: Discussionmentioning
confidence: 99%